2021
DOI: 10.7759/cureus.18109
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acotiamide Versus Mosapride in Patients With Functional Dyspepsia Associated With Meal-Induced Postprandial Distress Syndrome: A Phase III Randomized Clinical Trial

Abstract: Background: Acotiamide is a novel prokinetic drug that acts by enhancing the release of acetylcholine and is used in the treatment of functional dyspepsia-postprandial distress syndrome (FD-PDS). Mosapride is indicated to FD-PDS as per the Rome III treatment guidelines. Mosapride 5 mg three times daily (TID) is approved by the Drugs Controller General of India (DCGI) for the treatment of FD-PDS. The objective of this study was to determine the efficacy and safety of Acotiamide in comparison with Mosapride on F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…1 ). Four additional studies were included [ 3 , 4 , 11 , 12 ]. Noticeably, this review included 24 studies from the original systematic review [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ). Four additional studies were included [ 3 , 4 , 11 , 12 ]. Noticeably, this review included 24 studies from the original systematic review [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were nine studies from China with 1,665 participants [ 3 , 14 – 21 ], five studies from Belgium with 269 participants [ 22 – 26 ], one study from Germany with 548 participants [ 27 ], two studies from India with 280 participants [ 28 ] [ 12 ], six studies from Japan with 1778 participants [ 11 , 13 , 29 31 ], one study from Korea with 28 participants [ 32 ], one study from Denmark, Germany, France, Sweden, and the UK, with 566 participants [ 33 ], one study from Spain with 20 participants [ 4 ], and two studies from the US with 636 participants [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials have shown that ARB drugs can reduce the proportion of hypertensive patients who develop type 2 diabetes, and can signi cantly improve the prognosis of patients with high-risk hypertension, heart failure and diabetic nephropathy [6][7][8]. As a novel ARB drug, Azilsartan is mainly used for the treatment of adult hypertension [9]. As it binds to the angiotensin type II1 receptor (AT 1 ), which antagonizes angiotensin II and exhibits antihypertensive effects by mainly inhibiting the aldosterone secretion, strong vasoconstriction and other hypertensive effects, and by reducing the peripheral vascular resistance.…”
Section: Introductionmentioning
confidence: 99%